Physical, Degradable and Antibacterial Characteristics Of Chitosan/ Polyethylene Glycol /Nano hydroxyapatite scaffolds (Journal of University of Babylon for Engineering Sciences, 2023)
Tissue engineering has emerged as a promising alternative approach in the treatment of malfunctioning or lost organs. This method requires the use of a temporary scaffold to act as both a physical support system and an adhesive substrate for the transplanted cells, helping to direct the development of the new organs.Biodegradable scaffold system was prepared ‎using Chitosan (CS) ‎blended with another polymer ‎polyethylene glycol (PEG) at different ratios ‎‎(90%/10%, 80%/20%, 70%/30%) ‎respectively,  by casting method and the ‎‎(70/30) percent ratio was the best one due to its ideal properties and great flexibility. Then, three different ‎weight fractions of hydroxyapatite ‎nanoparticles (HANPs) were added to the ‎CS/PEG mixture to reinforce it (1, 2, and 3 ‎wt%). These nanocomposites were ‎evaluated using an FTIR spectrum, FE-‎SEM, AFM test, and biodegradable and antibacterial test. ‎The results of FTIR indicated good ‎interactions and created hydrogen bonding ‎between the compounds of ‎nanocomposites، FE-SEM scans showed a ‎well-integrated blend of CS and PEG with ‎good dispersion and embedding of HANPs.  AFM results shows the surface roughness of CS increases by adding 30%PEG, but the surface roughness decreases with increases the percent of nanoparticles HANPs. The degradation rate decreased with the addition of nanoHA. The antibacterial activity results show an increase as the concentrations of HANPs increase inhibition zone increases due to addition the Hydroxyapatite HANPs. although )70%:30%:3%)(CS/PEG/HANPs) ‎respectively it was the best sample in terms of results and the most suitable sample to be a biocompatible scaffold